Pylorectomy and Gastroduodenostomy (Billroth I Procedure) for Obstructive Antrum Pyloric Leiomyoma in a Bitch - Cima, Idalini; dos Santos, Alex; Dazzi, Claudia Cerutti; Machado, Tanise Policarpo; da Motta, Adriana Costa; Borges, Josiane; Rodriguez, Rubens; Silva, Marco Augusto Machado (Acta Scientiae Veterinariae, 2016)
Background: Gastric neoplasms are uncommon in dogs, especially those affecting smooth muscle layers. Leiomyoma is a smooth muscle benign neoplasm, which requires surgical resection. Pylorectomy and gastroduodenostomy (Billroth I procedure) is the most indicated technique in cases not affecting the biliary and pancreatic tracts. Thus, the purpose of this study was to report a successful case of Billroth I procedure in a bitch presenting antrum pyloric obstructive leiomyoma. Case: A 12-year-old, non-spayed, Cocker Spaniel bitch was admitted presenting depression, hyporexia, postprandial vomiting and sparse episodes of hematemesis, for 30 days. Clinical suspicion on obstructive gastric outflow disease was established. Bloodwork (complete blood count, BUN, albumin, ALP and ALT), abdominal ultrasound and thoracic radiographs were assessed. The patient undergone upper gastrointestinal endoscopy. On endoscopic evaluation, small hemorrhagic mucosa ulcers were visualized on the gastric body, antrum and pylorus. Moreover, a sessile, ulcerated, round-shape and infiltrated antral-pyloric mass was seen. The mass was 1.5-2.0 cm in diameter and apparently involved the smooth muscle layer, causing severe pyloric obstruction. However, endoscopic evaluation of the duodenum was possible. Several biopsy samples were taken from the neoplasm and sent for histopathologic assessment. The result was not conclusive due to low quality samples. The patient had progressive worsening of obstruction episodes and required surgery. A wide-margin pylorectomy and gastroduodenostomy (Billroth I procedure) was carried out. The retrieved specimen was sent to histopathological and immunohistochemistry (IHC) assessment. Positive staining for actin and desmin confirmed smooth muscle origin of the mass and histopathological assessment confirmed leiomyoma. The patient underwent regular periodic postoperative assessments, revealing progressive clinical improvement and normal weight gain. Control upper gastrointestinal endoscopy was performed. Gastric ulcers were completely healed and gastroduodenal anastomosis was functional. The anastomotic scar tissue was sampled and revealed chronic and normal healing process. Complete healing was confirmed and the patient was discharged. Discussion: Gastric neoplasms are not common in dogs. However, severe obstruction of gastric outflow is a potential risk for complications in those cases. Upper gastrointestinal endoscopic assessment is important not only for diagnosis, but also for surgery decision making. In the current study, gastroscopy provided accurate preoperative evaluation of severity of pyloric obstruction and diagnosis of secondary gastric ulcers. Direct visualization of lesions and multiple biopsy sampling were performed. The presence of neoplasms over 2-cm in diameter indicates need for complete laparoscopic or conventional surgical resection. In this case report, open resection was carried out due to prohibitive cost of laparoscopic approach, mass dimensions and probable involvement of deeper tissue layers. In conclusion, pylorectomy and gastroduodenostomy (Billroth I procedure) was curative and provided good prognosis following resection of an antrum pyloric obstructive leiomyoma. Endoscopy was critical for both diagnosis and decision-making towards surgery for gastric outflow obstruction due to an antrum pyloric neoplasm. Histopathological and immunohistochemistry assessment confirmed neoplasm type and assured oncological safety of resection with wide margins. Keywords: gastric neoplasms, smooth muscle tumor, endoscopy, dog.